2018
DOI: 10.1177/0142723717749073
|View full text |Cite|
|
Sign up to set email alerts
|

The relation between short-term memory and vocabulary skills in Greek children with cochlear implants: The role of hearing experience

Abstract: Weak performance in short-term memory (STM) in children with cochlear implants (CI) may have an impact on vocabulary development. Vocabulary, phonological STM (nonword repetition), phonological/verbal STM (digit span) and rapid naming measures were administered to 15 Greek-speaking children with CI (ages 4;6-8;6) and to chronological age (CA) and younger controls with normal hearing (NH). The children with CI exhibited lower performance in all tasks compared to CA controls but lagged behind only in phonologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 60 publications
(89 reference statements)
1
8
0
4
Order By: Relevance
“…Some studies (e.g. Briscoe et al, 2001; Dillon et al, 2004; Talli et al, 2018) found that English and Greek DHH children had impaired PSTM. Different results were obtained for Italian (Guasti et al, 2014).…”
Section: Memory Deficits In Dhh Childrenmentioning
confidence: 99%
See 4 more Smart Citations
“…Some studies (e.g. Briscoe et al, 2001; Dillon et al, 2004; Talli et al, 2018) found that English and Greek DHH children had impaired PSTM. Different results were obtained for Italian (Guasti et al, 2014).…”
Section: Memory Deficits In Dhh Childrenmentioning
confidence: 99%
“…Briscoe et al (2001) suggested that the lower performance of DHH children in NWR (but not in the FDS task) is not due to a compromised memory capacity, but to the computational overload required to process novel sound sequences through a deficient auditory system. Other studies suggested that poor performance and low scores in these measures may depend on the quality of received input, which is partial and degraded, and does not favour appropriate phonological representation of spoken language in short-term memory (Nittrouer et al, 2013; Pisoni et al, 2011; Talli et al, 2018).…”
Section: Memory Deficits In Dhh Childrenmentioning
confidence: 99%
See 3 more Smart Citations